Pemberdayaan Masyarakat melalui Edukasi dan Literasi: Konsep Pariwisata Halal di Desa Tegalsari - Muttaqin, Aminnullah Achmad; Satria, Dias; Hidayatuna, Aufa Shabrina; Rahmah, 'Aida Aulia; Suryawan, Helmi Bagus (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
Indonesia, with the largest Muslim population in the world, holds great potential in developing a sharia-based economy, including halal tourism. However, rural areas such as Tegalsari Village in Malang Regency have not fully optimized their local natural resources for halal tourism development. A community service program aimed to enhance community understanding of halal tourism and its economic opportunities. The program targeted village officials, local entrepreneurs, and youth representatives, employing a Participatory Action Research (PAR) approach. The main activity consisted of a one-day socialization involving 20 participants. Interactive discussions were also conducted to explore certification procedures, sharia-based economic practices, and village asset management. Reflection was carried out using a Likert-scale questionnaire to measure knowledge improvement, while evaluation was conducted through a pretest-posttest design analyzed using the Paired T-Test. The results indicated a significant increase in participants’ understanding of halal tourism concepts and local potential. Participants recognized that halal tourism is both religiously meaningful and strategically important to enhance village competitiveness, strengthen the local economy, and empower MSMEs. This program highlights that community involvement and knowledge dissemination are essential first steps in building sustainable and participatory halal tourism in rural areas.